CRITICAL DISCOURSE ANALYSIS IN THE ANTHOLOGY PERJAMUAN KHONG GUAN BY JOKO PINURBO - Faiz, Alfidiya; Seli, Sesilia; Saman, Sisilya (Jurnal Visi Ilmu Pendidikan, 2025)
This study aims to examine critical discourse analysis in Joko Pinurbo"™s anthology Perjamuan Khong Guan by employing Teun A. van Dijk"™s critical discourse analysis model. The research is grounded in a qualitative approach with a descriptive method, focusing on three dimensions of analysis: text, context, and social cognition. Research data were collected through note-taking, literature review, observation, interviews, and documentation of eight poems from the "Kaleng Satu" section of the anthology. The findings reveal that all data sources consistently represent Van Dijk"™s three dimensions of analysis. Pinurbo"™s poems depict social realities and the complexities of society through linguistic symbols that embody the poet"™s thoughts, emotions, and perspectives. The results affirm that poetry functions not only as an aesthetic expression but also as a medium of social critique erving a dual role as an artistic space and as a critical discourse that mirrors writing and lived realities. Furthermore, the study highlights the applicability of poetry in language and literature teaching, particularly in fostering students"™ contextual critical literacy and their understanding of literary texts as reflections of socio-cultural life.